1999
DOI: 10.1016/s0167-4889(99)00070-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane traffic and the cellular uptake of cholera toxin

Abstract: In nature, cholera toxin (CT) and the structurally related E. coli heat labile toxin type I (LTI) must breech the epithelial barrier of the intestine to cause the massive diarrhea seen in cholera. This requires endocytosis of toxin-receptor complexes into the apical endosome, retrograde transport into Golgi cisternae or endoplasmic reticulum (ER), and finally transport of toxin across the cell to its site of action on the basolateral membrane. Targeting into this pathway depends on toxin binding ganglioside GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
189
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 152 publications
8
189
0
1
Order By: Relevance
“…These results demonstrate that the internalization of the fluorescent GM 1 analog was perturbed by CtxB binding, and raise the possibility that internalization of endogenous GM 1 might also be affected by the bound toxin in some cell types. We speculate that this perturbation occurs because CtxB binding (five molecules of GM 1 bound per molecule of CtxB; Lencer et al, 1999) disrupts the normal interactions of GM 1 with neighboring lipids, proteins, and cholesterol that are required for clathrin-independent internalization.…”
Section: Ctxb (But Not Laccer) Internalization Mechanism Varies With mentioning
confidence: 99%
“…These results demonstrate that the internalization of the fluorescent GM 1 analog was perturbed by CtxB binding, and raise the possibility that internalization of endogenous GM 1 might also be affected by the bound toxin in some cell types. We speculate that this perturbation occurs because CtxB binding (five molecules of GM 1 bound per molecule of CtxB; Lencer et al, 1999) disrupts the normal interactions of GM 1 with neighboring lipids, proteins, and cholesterol that are required for clathrin-independent internalization.…”
Section: Ctxb (But Not Laccer) Internalization Mechanism Varies With mentioning
confidence: 99%
“…A Rentsendorj et al mediated cell entry, which is known to mediate internalization and retrograde trafficking of cholera toxin 28 and SV40, 29,30 and facilitate toxin arrival to the Golgi. We found that indeed PB partially overlaps with the caveolae marker, caveolin-1, during uptake (Figure 7e and f).…”
Section: Penton Base Traffickingmentioning
confidence: 99%
“…CTXB is enriched in biochemical lipid raft fractions and in caveolae (Fra et al, 1994;Parton et al, 1994;Parton, 1996;Smart et al, 1995;Schnitzer et al, 1996;Harder and Simons, 1997;Stauffer and Meyer, 1997;Henley et al, 1998;Orlandi and Fishman, 1998;Wolf et al, 1998;Lencer et al, 1999). Three GPI-anchored proteins, which are major components of detergentinsoluble raft fractions (Skibbens et al, 1989;Stefanova et al, 1991;Brown and Rose, 1992;Fiedler et al, 1993;Sargiacomo et al, 1993), were used as protein markers for lipid rafts.…”
Section: Plasma Membrane Distribution Of Lipid Raft Markers Detected mentioning
confidence: 99%